Effect of CRABP2 on the proliferation and odontoblastic differentiation of hDPSCs - Yanhong Yan; Shengcai Qi; Shi-qiang Gong; Guangwei Shang; Yumei Zhao (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract: Cellular retinoic acid-binding protein 2 (CRABP2) has been detected in several organs during embryonic development. Recent studies have demonstrated that CRABP2 plays important roles in the retinoic acid, β-catenin and Notch signaling pathways, as well as in the interaction between epithelial and mesenchymal cells, which are important for human dental pulp stem cells (hDPSCs) and tooth development. In the present study, the expression of CRABP2 during mouse molar development and the role of CRABP2 in hDPSC odontoblastic differentiation were evaluated. CRABP2 was gradually decreased during the development of the first maxillary molar, which exhibited the same trend as the expression of CRABP2 during the odontoblastic induction of hDPSCs. CRABP2 knockdown inhibited the proliferative ability of hDPSCs, while it enhanced odontoblastic differentiation via promoting mineralization nodule formation and upregulating the activity of alkaline phosphatase and the expression of mineralization-related genes. The present study uncovered a novel function of CRABP2 in hDPSCs. Our data suggest that CRABP2 may act as a regulator during the proliferation and differentiation of hDPSCs.